Preliminary Recognition of River Infrastructure - Mahendra Andiek Maulana; Hitapriya Suprayitno; Ria Asih Aryani Soemitro (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
River infrastructures can be defined as facilities and structures that support all activities related to river. Many infrastructures that exist along river stream but few of them are listed and recognized as an important part in the river system. The condition of assets that support the river function should be considered since it determines the sustainability of water supply system for many areas. Starting from upstream, there were dam and reservoir that constructed to reserve the water. Moreover, the water can be distributed to the downstream area for many requirements, such as irrigation system, hydro power, industrial process, etc. In the other hand, dam and reservoir also functioned as flood control that protect the downstream area from flood and inundation. In alluvial river, there were erosions that occurs as river flow velocity could transported soft soil numerously. Hence, the river bank protections were built in order to protect the nearby river infrastructures. Therefore, the infrastructures recognition as preliminary assessment to the river asset management need to be done in order to maintain the river system.